Physical activity has decreased in Finnish children and adolescents from 2016 to 2022 - Pauliina Husu; Kari Tokola; Henri Vähä-Ypyä; Harri Sievänen; Sami Kokko; Jari Villberg; Tommi Vasankari (BMC Public Health, 2024)
Abstract Background Varying trends in children’s and adolescents’ physical activity (PA) have been reported during the last 10–20 years. Trends in sedentary behavior (SB) have been studied only rarely. The purpose of the present study was to describe population-based trends in accelerometer-measured PA, standing and SB, among Finnish 7-15-year-old children and adolescents, and to evaluate the potential influence of the COVID-19 pandemic on these behaviors. Method A cross-sectional population-based Finnish school-aged physical activity Study (FSPA) measured daily steps, vigorous (VPA), moderate (MPA), moderate-to-vigorous (MVPA), light physical activity (LPA), standing, and SB by an accelerometer for seven consecutive days in 2016, 2018, and 2022 (n = 7.080, 57% girls). The data was analyzed by multivariate regression analysis. Results In 2016, participants took on average 10.305 steps per day, and spent 0:15 (h: min) in VPA, 1:37 in MPA, 1:52 in MVPA, 3:48 in LPA, 0:55 in standing and 7:52 in SB. From 2016 to 2018, daily steps, MPA, LPA, and standing increased [229 steps (95% Confidence Interval, CI 70–387), 0:03 (CI 0:01 − 0:04), 0:11 (CI 0:09 − 0:14), and 0:07 (CI 0:05 − 0:08), respectively], while VPA and SB decreased [0:01 (CI 0:00–0:02) and 0:20 (CI 0:16 − 0:24), respectively]. From 2018 to 2022, daily PA and standing declined [751 steps (CI 562–939), VPA 0:02 (CI 0:01 − 0:03), MPA 0:09 (CI 0:07 − 0:11), MVPA 0:11 (CI 0:09 − 0:14), LPA 0:08 (CI 0:05 − 0:11), and standing 0:01 (CI 0:01 − 0:03)] while SB increased 0:21 (CI 0:16 − 0:25) indicating potential influence of the pandemic. Conclusions Children and adolescents became physically less active from 2016 to 2022. The potential effects of the COVID-19 were seen as declined PA and increased sedentariness from 2018 to 2022.